Throughput Maximization Based on Rate-Splitting Multiple Access for Next-Generation LEO Satellite Network - 류재학 (The Graduate School, Ajou University, 2024)
With the rapid development of satellite technology and in- creasing demand for massive connectivity, the satellite net- work has received significant attention as a main component in future communication networks. Specifically, low Earth or- bit (LEO) satellites, positioned at relatively lower altitudes, have been the subject of intensive research due to their abil- ity to offer lower latency and higher data rates. However, de- spite the exponential increase in LEO satellites in space, the available spectrum resource remains inherently limited. To alleviate the spectrum scarcity, the frequency coexistence be- tween geostationary orbit (GEO) and LEO satellite systems has emerged as a promising strategy. Note that this approach of frequency coexistence confronts mutual interference, which could potentially compromise the system throughput for GEO- LEO coexisting satellite systems (CSS). Particularly, in-line interference, caused by the movement of LEO satellites near the line-of-sight (LOS) path between GEO satellite and GEO users (GUs), can significantly degrade GEO system through- put. Rate-splitting multiple access (RSMA) framework has proven to be a robust solution for interference management. In this paper, we put forth a novel RSMA with a super- common message for LEO-GEO coexisting satellite systems (CSS). The employment of a super-common message, which can be decoded by both GUs and LEO users (LUs), pro- vides a means for GUs to mitigate in-line interference via the successive interference cancellation (SIC) technique. Further- more, we formulate a traffic-aware throughput maximization (TTM) problem aiming to maximize system throughput for given imbalanced traffic demands among users. As a result, the TTM precoder is flexibly adjusted to accommodate both the interference leakage from LEO satellite to GUs and target traffic demands. The numerical results demonstrate that the proposed framework guarantees seamless services for LEO- GEO CSS even in the in-line interference regime.
학위논문(석사)--AI융합네트워크학과,2024. 2
Keywords: Satellite communication; rate-splitting multiple access; semi-definite relaxation